Evaluate:
π 2 1 ∫ 0 ∞ x ( 1 − x ) 2 ( ln x ) 2 d x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Again Brilliant got me. After a solution is entered, the next step is to look at the other solutions. Instead of giving credit for a solved problem, Brilliant says you cheated, Bah, humbug! (A reference to the Christmas Carol by Charles Dicken's.)
π 2 ∫ x ( 1 − x ) 2 lo g 2 ( x ) d x ⇒ 2 π 2 − 8 Li 3 ( − x ) + 8 Li 3 ( x ) + 4 Li 2 ( − x ) ( lo g ( x ) − 2 ) − 4 Li 2 ( x ) ( lo g ( x ) − 2 ) − lo g ( 1 − x ) lo g 2 ( x ) + lo g ( x + 1 ) lo g 2 ( x ) + 1 − x lo g 2 ( x ) − x + 1 lo g 2 ( x ) + 4 lo g ( 1 − x ) lo g ( x ) − 4 lo g ( x + 1 ) lo g ( x )
The limit of the above indefinite integral as x goes to 0 is 0.
The limit of the above indefinite integral as x goes to infinity is 2.
@Chew-Seong Cheong,@Jon Haussmann, please post your solution as I am tired trying this one.
I have solved it. how should i post the photo of my solution?
@Aditya Kumar , when you begin to write your solution, you will see 7 different symbols above in a column. Click on 3rd sign from which you can upload your jpg file. Anyway can you give some insight how you started.
Put x=t^2 and then z=1/t and then break the limits from 0to 1 and 1 to infinity and then apply by parts and after that series expansion. To be honest,i couldn't solve it in AITS .But solved it at home . don't you think such kind of problems are irrelevant for jee.
@Aditya Kumar , it's becoming difficult. After splitting in two integrals, which one to be chosen for by parts? Which one to assume 1st and 2nd function? Can you post the photo? Yes they are irrelevant for jee but they are given to enhance your thinking capability to another level. So it helps in some way. You become habitual of these problems and then jee will seem like a normal easy exam.
Problem Loading...
Note Loading...
Set Loading...
first split the integral in 2: ∫ 0 ∞ x ( 1 − x ) 2 ln 2 ( x ) dx = ∫ 0 1 x ( 1 − x ) 2 ln 2 ( x ) dx + ∫ 1 ∞ x ( 1 − x ) 2 ln 2 ( x ) dx = ∫ 0 1 x ( 1 − x ) 2 ln 2 ( x ) dx + ∫ 0 1 ( 1 − x ) 2 ln 2 ( x ) x dx = ∫ 0 1 x ( 1 − x ) 2 ln 2 ( x ) ( 1 + x ) dx the reason the integral was split in two was so that the bound would be from 0 to 1, allowing the use of the taylor series: ( 1 − x ) 2 1 = n = 1 ∑ ∞ n x n − 1 , ∣ x ∣ ≤ 1 plugging this in the integral and interchanging summation and integral signs: n = 1 ∑ ∞ n ∫ 0 1 ln 2 ( x ) x n − 3 / 2 + ln 2 ( x ) x n − 1 / 2 dx using I ( a ) = ∫ 0 1 x a dx = a + 1 1 → I ′ ′ ( a ) = ∫ 0 1 x a ln 2 ( x ) dx = ( a + 1 ) 3 2 ∫ 0 1 ln 2 ( x ) x n − 3 / 2 + ln 2 ( x ) x n − 1 / 2 dx = ( n − 1 / 2 ) 3 2 + ( n + 1 / 2 ) 3 2 note differentiation under the integral sign was used. now the sum becomes n = 1 ∑ ∞ ( ( n − 1 / 2 ) 3 2 n + ( n + 1 / 2 ) 3 2 n ) = n = 1 ∑ ∞ ( ( n − 1 / 2 ) 3 2 n + ( n − 1 / 2 ) 3 2 ( n − 1 ) ) = n = 1 ∑ ∞ ( ( n − 1 / 2 ) 3 4 n − 2 ) = n = 1 ∑ ∞ ( ( n − 1 / 2 ) 2 4 ) = n = 1 ∑ ∞ ( ( 2 n − 1 ) 2 1 6 ) = 1 6 ζ ( 2 ) ( 1 − 2 − 2 ) = 2 π 2